1976
DOI: 10.1002/asna.19762970108
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen des Lichtwechsels von zwölf Ap‐Sternen in zehn Spektralbereichen

Abstract: Z e n t r a l i n s t i t u t ftir Astrophysik d e r Akademie d e r Wissenschaften der DDR Mit 15 Abbildungen. (Eingegangen 1975 Juli 11)Twelve Ap stars with known periods and fairly large amplitudes were photoelectrically investigated in a ten colour system (A 3400 A to A7600 A). The amplitude-wavelength relations following from the light curves cannot be explained by the influence of the backwarming effect. These relations point to complicated structures in the atmospheres of the peculiar regions of the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Also, we obtained some observations as private communications from authors. The 102 mCP listed stars were observed in the Strömgren photometric system (Strömgren 1966) and observations were also performed in other photometric systems, e.g., the Johnson international photometric system (Johnson & Morgan 1951), the HIPPARCOS (ESA 1997), Geneva (Golay 1972), Shemakha 10-colour photometry (Schöneich, Hildebrandt & Fuertig 1976), Walraven (Walraven & Walraven 1960), and Maitzen (Maitzen 1976) systems. We expect the list to be extended to more than 250 stars with photometric observations.…”
Section: Structure and Content Of The Databasementioning
confidence: 99%
“…Also, we obtained some observations as private communications from authors. The 102 mCP listed stars were observed in the Strömgren photometric system (Strömgren 1966) and observations were also performed in other photometric systems, e.g., the Johnson international photometric system (Johnson & Morgan 1951), the HIPPARCOS (ESA 1997), Geneva (Golay 1972), Shemakha 10-colour photometry (Schöneich, Hildebrandt & Fuertig 1976), Walraven (Walraven & Walraven 1960), and Maitzen (Maitzen 1976) systems. We expect the list to be extended to more than 250 stars with photometric observations.…”
Section: Structure and Content Of The Databasementioning
confidence: 99%
“…The light variability of this star has been studied by Jarzebowski (1960), Chugainov (1961), Stepien (1968), van Genderen (1971, Panov & Schöneich (1975), Schöneich et al (1976), Rakosch & Fiedler (1978), Hempelmann (1981), and Catalano & Leone (1994). All these authors have confirmed the value 6.009 d of the period as given by Babcock (1958a).…”
Section: Hd 153882 = Hr 6326 = V451 Hermentioning
confidence: 69%
“…The mean wavelengths and halfwidths of the Strömgren (1963) intermediate bandwidth filters are summarized in Table 2, which also includes the values of the 10-color photometric system (Schöneich et al 1976) that is discussed in Section 4.16. In this paper, we are using the Strömgren bandpasses to study light variations using differential photometry.…”
Section: Observationsmentioning
confidence: 99%
“…The á ñ W W plot represents the normalized Sr/Mg/Ti equivalent widths from Floquet (1977). ( Table 3). The effective wavelengths and bandwidths for the 10-color system (Schöneich et al 1976) used by Schöneich & Zelwanowa are summarized in Table 2. As can be seen in Figure 11, the U, X, Y, and V light curves vary with u, v, b, and y, except that Y may be fainter than b at phase 0.0.…”
Section: Hd 221568 = V436 Casmentioning
confidence: 99%